Microstructural and Compositional Features of the Fibrous and Hyaline Cartilage on the Medial Tibial Plateau Imply a Unique Role for the Hopping Locomotion of Kangaroo - He, Bo; Wu, Jian Ping; Xu, Jiake; Day, Robert; Kirk, Thomas (PLOS, 2013)
Hopping provides efficient and energy saving locomotion for kangaroos, but it results in great forces in the knee joints. A previous study has suggested that a unique fibrous cartilage in the central region of the tibial cartilage could serve to decrease the peak stresses generated within kangaroo tibiofemoral joints. However, the influences of the microstructure, composition and mechanical properties of the central fibrous and peripheral hyaline cartilage on the function of the knee joints are still to be defined. The present study showed that the fibrous cartilage was thicker and had a lower chondrocyte density than the hyaline cartilage. Despite having a higher PG content in the middle and deep zones, the fibrous cartilage had an inferior compressive strength compared to the peripheral hyaline cartilage. The fibrous cartilage had a complex three dimensional collagen meshwork with collagen bundles parallel to the surface in the superficial zone, and with collagen bundles both parallel and perpendicular to the surface in the middle and deep zones. The collagen in the hyaline cartilage displayed a typical Benninghoff structure, with collagen fibres parallel to the surface in the superficial zone and collagen fibres perpendicular to the surface in the deep zone. Elastin fibres were found throughout the entire tissue depth of the fibrous cartilage and displayed a similar alignment to the adjacent collagen bundles. In comparison, the elastin fibres in the hyaline cartilage were confined within the superficial zone.This study examined for the first time the fibrillary structure, PG content and compressive properties of the central fibrous cartilage pad and peripheral hyaline cartilage within the kangaroo medial tibial plateau. It provided insights into the microstructure and composition of the fibrous and peripheral hyaline cartilage in relation to the unique mechanical properties of the tissues to provide for the normal activities of kangaroos.